Pengaruh Penerapan Pendekatan Berdiferensiasi Berbasis Model Problem Based Learning Terhadap Hasil Belajar Matematika Siswa Kelas IV SD Kecamatan Rao Selatan Kabupaten Pasaman - Syiamfitri, Lailatil; Firman, Firman; Desyandri, Desyandri (Universitas Pahlawan Tuanku Tambusai, 2024)
There are no students in the same class. They come from different backgrounds, have different learning preferences, different interests, or learn at different paces so their readiness to learn is different. This learning practice is important to share because it is expected to provide benefits related to the application of learning in elementary schools. Different learning in this study uses the Problem Based Learning (PBL) Model. The strategy used in this case is differentiated by Learning is to map learning needs based on three aspects, namely learning readiness, learning interests, and student learning profiles using surveys filled out through smartphones. Then the author plans different learning based on the mapping results, namely providing a variety of options for strategies, materials, and ways to learn. The learning results that have been carried out are that students are very happy and enthusiastic in participating in learning from beginning to end. The differentiated learning carried out is able to accommodate the learning needs of students in one class.